Body Composition of Very Low‐Birth‐Weight Infants Fed Fortified Human Milk: A Pilot Study. Issue 4 (24th June 2020) - McNelis, Kera; Liu, Chunyan; Ehrlich, Shelley; Fields, Christopher; Fields, Trayce; Poindexter, Brenda
Abstract: Background: Although donor milk is increasingly fed to preterm infants, the resultant quality of growth and body composition is unknown. The aim of this pilot study was to describe the body composition of very low‐birth‐weight infants fed human milk in the neonatal intensive care unit and explore the association between the proportion of donor human milk intake and fat‐free and fat mass deposition. Methods: Body composition of 30 preterm infants fed maternal and donor human milk was measured by air displacement plethysmography. Regression models were developed to associate each parameter of body composition with the proportion of donor milk intake and other explanatory variables. Results: The proportion of donor milk intake was negatively associated with body fat percentage ( P = .01). Fat‐free mass z ‐scores ranged from −4.6 to 1.11 (mean z ‐score of −0.95, 17th percentile). Conclusion: Donor human milk intake is negatively associated with body fat percentage in this pilot study of very low‐birth‐weight preterm infants.